2002
DOI: 10.1038/sj.bjc.6600152
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect on expression of angiogenic factors by antiangiogenic agents in renal cell carcinoma

Abstract: Since it has been widely recognised that renal cell carcinoma is refractory to standard therapies such as chemotherapy and radiotherapy, a new modality of treatment is needed. One of the potential alternative therapies for renal cell carcinoma may be inhibition of angiogenesis. In this study, we analysed the inhibitory effects of several potential agents on expression of angiogenic factors such as vascular endothelial growth factor and basic fibroblast growth factor, which are the main mediators in angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…However, it has been reported that ocular-infiltrating T cells could produce IFN-g 24,25 and IFN-g has been shown to have some antiangiogenic activity through a regulation of the angiogenic factors (eg VEGF, FGF). 22,23 However, in contrast to the theory presented above, another possible mechanism might explain the retinal abnormalities in IL-18 KO mice: endogenous IL-18 might promote vascular network formation, as IL-18 is known to accelerate endothelial cell migration and tube formation in vitro. 11 Our study revealed expanding areas of nonperfusion in IL-18 KO mouse retinas at P14 (Figure 2c and d).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…However, it has been reported that ocular-infiltrating T cells could produce IFN-g 24,25 and IFN-g has been shown to have some antiangiogenic activity through a regulation of the angiogenic factors (eg VEGF, FGF). 22,23 However, in contrast to the theory presented above, another possible mechanism might explain the retinal abnormalities in IL-18 KO mice: endogenous IL-18 might promote vascular network formation, as IL-18 is known to accelerate endothelial cell migration and tube formation in vitro. 11 Our study revealed expanding areas of nonperfusion in IL-18 KO mouse retinas at P14 (Figure 2c and d).…”
Section: Discussionmentioning
confidence: 42%
“…IFN-g has been reported to inhibit tumor angiogenesis; [21][22][23] therefore, it might regulate the formation of retinal vessels. IFN-g mRNA was present at low levels in the IL-18 KO mice, even at P14.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a reduces urokinase-type plasminogen activator and plasminogen activator inhibitor-1 activity (135) and significantly inhibits MMP-9 enzymatic activity and protein expression (136). IFN-a and IFN-h treatment also inhibits angiogenesis by down-regulation of bFGF expression (137)(138)(139), but other studies suggest that the action of IFN-a is not mediated by bFGF or VEGF (140)(141)(142).…”
Section: Non-matrix-derived Inhibitors Of Angiogenesismentioning
confidence: 99%
“…Hypoxic conditions were generated by using the BBL GasPak Pouch System (BD Biosciences), as recently described, which reduces oxygen to less than 2%. 23,24 Human umbilical vein ECs (HUVECs) were freshly isolated from human umbilical veins of newborns by collagenase digestion. 25 HUVECs and bovine aortic endothelial cells (BAECs) were cultured in ECGM (PromoCell) containing 10% heat-inactivated FCS and antibiotics.…”
Section: Antibodies Plasmids Growth Factors Drugs Cells and Mediamentioning
confidence: 99%